Efektivitas Latihan Otot Kegel terhadap Elastisitas Otot Panggul sebagai Pencegahan Ruptur Perineum di Puskesmas Perawatan Tiley Pulau Morotai - Indriyanti Utok; Rani Safitri (Calory Journal Medical Laboratory Journal, 2025)
Childbirth is a series of natural processes that trigger various changes in the mother's body so that she can deliver her baby through the birth canal. Perineal stiffness can actually be anticipated and prevented early in pregnancy, one way is through physical exercises such as pregnancy yoga. Pregnancy yoga has many benefits, especially in alleviating complaints during pregnancy, reducing anxiety, improving sleep quality, and preparing the physical condition before childbirth by strengthening and increasing the elasticity of the pelvic floor muscles, so that the birth process becomes easier. This study aims to analyze the effect of prenatal gentle yoga on the incidence of perineal tears in mothers who will give birth in the work area of ​​the Tiley Health Center on Morotai Island. This study used a quasi-experimental method with a posttest control design. The sample used in the study consisted of mothers giving birth who met certain inclusion criteria, with a total of 36 pregnant women. The instruments used in this study were the Kegel Exercise SOP observation sheet and the assessment of the level of perineal tears. Data were analyzed using the Mann-Whitney statistical test. The results showed a distribution of respondents regarding Kegel exercises: 18 respondents (50%) performed Kegel exercises and 18 respondents (50%) did not. The highest rates of perineal rupture were grade I and grade II, with 13 respondents (36.1%) each. The resulting p-value was 0.0001 (p < 0.05), indicating a significant effect of Kegel exercises on the rate of perineal rupture in primiparous women.